The Impact of Curriculum Differences on Infection Control Knowledge and Practice Among Healthcare Students in Saudi Arabia. - Mersal, Fathia Ahmed; Said, Fathia Gamal El; Alanazi, Fadiyah Jadid; Alenezi, Ibrahim Naif; Alanazi, Faisal Khalaf; Green, Cheryl (Nursing Forum, 2026)
Background: Healthcare‐associated infections represent a significant global challenge, with healthcare students playing a crucial future role in prevention efforts. While previous research has examined infection control knowledge among students, few studies have explored the complex interplay between educational curriculum factors, knowledge domains, and actual practice behaviors across multiple healthcare disciplines simultaneously. Aim: To compare IPC knowledge and practices among nursing, medical, and applied medical sciences students at a Saudi university, while exploring curricular influences on competency gaps. Methods: This single‐institution study used a comparative cross‐sectional approach. It employed quota sampling to recruit 304 healthcare students from nursing, medical, and applied science programs at Northern Border University, Arar, Saudi Arabia. Data collection used a validated three‐part assessment tool examining demographic characteristics and curriculum exposure, infection prevention and control (IPC) knowledge, and self‐reported IPC practices. Results: Medical students exhibited the highest theoretical knowledge (83.7%), while nursing students reported superior practical compliance (96.3%). Applied medical sciences students lagged in practical training integration (62.5%). College affiliation (β = −0.968, p = 0.02), practical clinical training, and practice scores (p < 0.001) significantly predicted outcomes. Conclusion: Disparities in IPC competency result from differences in the clinical experience included in the curriculum. To align with the healthcare quality and safety objectives of Saudi Vision 2030, it is necessary to provide interventions that are specific to the discipline, such as training based on simulation for students studying applied medical sciences.